Equilibrium pattern model for learning. (17th August 2009) - Sarirete, Akila; Noble, Elizabeth; Chikh, Azeddine
Contemporary students are characterised by having applied learning styles and methods of acquiring knowledge. This behaviour is consistent with the constructivist models, where students are co-partners in the learning process. In the present work the authors developed a new model of learning based on the constructivist theory coupled with the cognitive development theory of Piaget. The model considers first the level of learning based on several stages and secondly, the move from one stage to another and thirdly the movement requires the instructor to challenge the learners' understanding. Each time a new concept is introduced, it creates a disequilibrium that needs to be worked out to return back to the equilibrium stage. This process of 'disequilibrium/equilibrium' has been analysed and validated using a course in Computer Networking as part of the Cisco Networking Academy Program at Effat University in Saudi Arabia. The model provides a theoretical foundation for teaching, especially in a complex knowledge domain such as engineering, and can be used in a knowledge economy.